Odpowiedź :
a)
[tex]2x - 3 = 8[/tex]
[tex]2x = 8 + 3[/tex]
[tex]2x = 11[/tex]
[tex]x = \frac{11}{2} = 5 \frac{1}{2} [/tex]
b)
[tex]4x = 5x - 2[/tex]
[tex]4x - 5x = - 2[/tex]
[tex] - x = - 2[/tex]
[tex]x = 2[/tex]
c)
[tex]5x - 12 = 4 + 4x[/tex]
[tex]5x - 4x = 4 + 12[/tex]
[tex]x = 16[/tex]
d)
[tex]9x - 8 = 3x + 2[/tex]
[tex]9x - 3x = 2 + 8[/tex]
[tex]6x = 10[/tex]
[tex]x = \frac{10}{6} = \frac{5}{3} = 1 \frac{2}{3} [/tex]
e)
[tex]10x - 4 = 5x + 8[/tex]
[tex]10x - 5x = 8 + 4[/tex]
[tex]5x = 12[/tex]
[tex]x = \frac{12}{5} = 2 \frac{2}{5} [/tex]
f)
[tex]2x - 2 = 12x + 18[/tex]
[tex]2x - 12x = 18 + 2[/tex]
[tex] - 10x = 20[/tex]
[tex]x = - 2[/tex]
g)
[tex]4 - 5(x + 2) = 3 - 5x[/tex]
[tex]4 - 5x - 10 = 3 - 5x[/tex]
[tex] - 5x + 5x = 3 - 4 + 10[/tex]
[tex]0 = 9[/tex]
równanie sprzeczne, 0 ≠ 9
h)
[tex]6x - 3 = 2x + 5[/tex]
[tex]6x - 2x = 5 + 3[/tex]
[tex]4x = 8[/tex]
[tex]x = 2[/tex]
i)
[tex]2x + 6 = 12[/tex]
[tex]2x = 12 - 6[/tex]
[tex]2x = 6[/tex]
[tex]x = \frac{6}{2} = 3[/tex]
j)
[tex]3x - 4 = 17[/tex]
[tex]3x = 17 + 4[/tex]
[tex]3x = 21[/tex]
[tex]x = \frac{21}{3} = 7[/tex]
k)
[tex]4 - 2x = 10[/tex]
[tex] - 2x = 10 - 4[/tex]
[tex] - 2x = 6[/tex]
[tex]x = \frac{6}{ - 2} = - 3[/tex]
l)
[tex]x + 6 = 2x + 3[/tex]
[tex]x - 2x = 3 - 6[/tex]
[tex] - x = - 3[/tex]
[tex]x = 3[/tex]
m)
[tex]2x + 4 = 4 - 3x[/tex]
[tex]2x + 3x = 4 - 4[/tex]
[tex]5 x = 0[/tex]
[tex]x = \frac{0}{5} = 0[/tex]
n)
[tex]3x + 11 = 6x - 1[/tex]
[tex]3x - 6x = - 1 - 11[/tex]
[tex] - 3x = - 12[/tex]
[tex]x = \frac{ - 12}{ - 3} = 4[/tex]
o)
[tex]2(x + 1) = 5[/tex]
[tex]2x + 2 = 5[/tex]
[tex]2x = 5 - 2[/tex]
[tex]2x = 3[/tex]
[tex]x = \frac{3}{2} = 1 \frac{1}{2} [/tex]
p)
[tex]2(x + 4) = 8 + 2x[/tex]
[tex]2x + 8 = 8 + 2x[/tex]
[tex]2x - 2x = 8 - 8[/tex]
[tex]0 = 0[/tex]
jest to równanie tożsamościowe
q)
[tex]2x - (3x + 1) = 6[/tex]
[tex]2x - 3x - 1 = 6[/tex]
[tex]2 x - 3x = 6 + 1[/tex]
[tex] - x = 7[/tex]
[tex]x = \frac{7}{ - 1} = - 7[/tex]
r)
[tex]2(x + 1) + x = 3x[/tex]
[tex]2x + 2 + x = 3x[/tex]
[tex]2x + x - 3x = - 2[/tex]
[tex]0 = - 2[/tex]
równanie sprzeczne, 0 ≠ -2
s)
[tex]2 - (5 + x) = 2(3 - x)[/tex]
[tex]2 - 5 - 5 = 6 - 2x[/tex]
[tex]2x = 6 - 2 + 5 + 5[/tex]
[tex]2x = 14[/tex]
[tex]x = \frac{14}{2} = 7[/tex]
a) 2x = 8 + 3
2x = 11 / ;2
X = 5,5
b) 4x = 5x - 2
4x - 5x = -2
-1x = -2 / : (-1)
X= 2
c) 5x -12 = 4 + 4x
5x - 4 = 4 + 12
1x = 16 / : (-1)
X= 16
d) 9x - 8 = 3x +2
9x - 3x = 2 + 8
6x = 10 /:(-6)
X = -1,66
e) 10x - 4 = 5x +8
10x - 5x = 8 + 4
5x = 12 /:(-5)
x = -2,4
f) 2x - 2 = 12x + 18
2x - 12x = 18 + 2
-10x = 20 /:(-10)
x = 2
g) 4 - 5(x+2) = 3 - 5x
4 - 5x + 10 = 3 - 5x
-5 + 5x = 3 -4 - 10
x = 0
h) 6x - 3 = 2x + 5
6x - 2x = 5 + 3
4x = 8 /:(-4)
x = -2
i) 2x + 6 = 12
2x = 12 - 6
2x = 6 /:(-2)
x = -3
j) 3x - 4 = 17
3x = 17 + 4
3x = 21 /:(-3)
x = -7
k) 4 - 2x = 10
-2x = 10 - 4
-2x = 6 /:(-2)
x = -3
l) x + 6 = 2x + 3
x - 2x = 3 - 6
-1x = -3 /:(-1)
x = 3
m) 2x + 4 = 4 - 3x
2x + 3x = 4 - 4
5x = 0
x = 0
n) 3x + 11 = 6x - 1
3x - 6x = -1 - 11
-3x = -12 /:(-3)
x = 4
o) 2(x+1) = 5
2x + 2 = 5
2x = 5 - 2
2x = 3 /:(-2)
x = -1,5
p) 2(x+4) = 8 + 2x
2x + 8 = 8 + 2x
2x - 2x = 8 - 8
x(0) = 0
q) 2x - (3x + 1) = 6
2x - 3x + 1 = 6
2x - 3x = 6 - 1
-1x = 5 /:(-1)
x = -5
r) 2(x+1) + x = 3x
2x + 2 + x = 3x
2x + x - 3x = -2
x = -2
s) 2 - (5 + x) = 2(3-x)
2 - 5 + x = 6 - 2x
x + 2x = 6 -2 + 5
3x = 9 / :(-3)
x = -3